2006
DOI: 10.1086/498560
|View full text |Cite
|
Sign up to set email alerts
|

The Discordance of Mass‐Loss Estimates for Galactic O‐Type Stars

Abstract: We have determined accurate values of the product of the mass-loss rate and the ion fraction of P 4+ ,Ṁ q(P 4+ ), for a sample of 40 Galactic O-type stars by fitting stellar-wind profiles to observations of the P v resonance doublet obtained with FUSE, ORFEUS/BEFS, and Copernicus. When P 4+ is the dominant ion in the wind (i.e., 0.5 q(P 4+ ) ≤ 1),Ṁ q(P 4+ ) approximates the mass-loss rate to within a factor of 2. Theory predicts that P 4+ is the dominant ion in the winds of O7-O9.7 stars, though an empirical e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
417
3
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(463 citation statements)
references
References 68 publications
39
417
3
4
Order By: Relevance
“…Since Vink et al predict an increase inṀ of a factor of five, this would imply that the clumping factors for hotter objects are larger by factors of 4 (most optimistic case) to 156 (worst case) compared to those of cooler ones 20 . Given our present knowledge (see Fullerton et al 2006;Puls et al 2006, and references therein), this is not impossible, but raises the question about the physical origin of such a difference. This hypothesis would also imply that all B-SG mass-loss rates are overpredicted, though to a lesser extent for cooler subtypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since Vink et al predict an increase inṀ of a factor of five, this would imply that the clumping factors for hotter objects are larger by factors of 4 (most optimistic case) to 156 (worst case) compared to those of cooler ones 20 . Given our present knowledge (see Fullerton et al 2006;Puls et al 2006, and references therein), this is not impossible, but raises the question about the physical origin of such a difference. This hypothesis would also imply that all B-SG mass-loss rates are overpredicted, though to a lesser extent for cooler subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…However, recent observational studies of clumping in O-SGs have revealed inconsistencies both between results originating from different wind diagnostics, such as UV resonance lines, H α and the IR-/radioexcess (Fullerton et al 2006;Puls et al 2006), and between theoretical predictions and observed constraints on the radial stratification of the clumping factor (Bouret et al 2005;Puls et al 2006). In addition, there are observational results which imply that clumping might depend on wind density.…”
Section: Introductionmentioning
confidence: 99%
“…We next consider whether the observed variability in the absorbing column could be due to wind structures, and how the characteristics of those structures compare to what is known about radiatively driven winds in other contexts, such as clumps (Abbott et al 1981;Hillier & Miller 1998;Fullerton et al 2006;Puls et al 2006) or discrete absorption components (DACs; Prinja & Howarth 1986). To this end, we use a numerical code to simulate the column density between the observer and a point-like X-ray source, as the source orbits around a companion whose wind is composed of discrete clumps.…”
Section: Clumpy Wind Model For the Hard Statementioning
confidence: 99%
“…For the resonance lines P v λλ1118, 1128, N v λλ1239, 1243, Si iv λλ1394, 1403, and C iv λλ1548, 1551, it is well known that the crucial parameter needed to fit the profiles is the line optical depth which is directly proportional to the mass-loss rate and the respective ionization fraction (see for instance the case of P v λλ1118, 1128 in Fullerton et al 2006). …”
Section: Winds Highly Ionized By X-raysmentioning
confidence: 99%